FTA supports the development of the Sri Lanka Green Climate Fund Operation Manual and Stakeholder Engagement Strategy - CGIAR Research Program on Forests, Trees and Agroforestry (2021)
The Operation Manual and Stakeholder Engagement Strategy provide simplified and practical guidelines to all stakeholders about the Green Climate Fund (GCF), its modalities and procedures in Sri Lankan context.